Leitura e Provinha Brasil: dos pressupostos teóricos ao diagnóstico de habilidades - Santos, Solange dos (2014)
The difficulties related to reading skills identified in the results of assessments as ENEM, SAEB, PISA, pointed up the need to analyze the reasons causing the failure in the readers´ formation, especially in the initial grades. The |Provinha Brasil| becomes the focus of analysis, is a diagnostic assessment nationwide, which indicates the level of alphabetization and literacy of students, assessing the reading skills of students in 2nd year of elementary school in public schools. In addition, the results of |Provinha Brasil| provide subsidies for educational planning and the choice of teaching materials. Along this perspective, this study has as its focus observing how the reading is treated in |Provinha Brasil|. For both, it became necessary to make reflections on reading, especially in the initial grades, emphasizing the notions of alphabetization and literacy, the importance of diversity of genres for teaching reading and how all this is dealt in the official texts. With respect to |Provinha Brasil|, described its objectives, theoretical assumptions and methodology, beyond an examination of the issues of the tests 1 and 2 of the 2013 edition. It could be observed that the |Provinha Brasil| conceive reading as a social practice that goes beyond decoding, covering specificities of alphabetization and literacy. In the |Provinha Brasil|, despite little space for skills relating to the axis of reading, inferential issues predominate. Therefore, this study reaffirms the view that reading practices in schools and their teaching materials remains an open question to new studies that provide new evolutions in the teaching-learning process of reading.